The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ma12233909
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Assisted Joining of Sheets to Tubes by Annular Sheet Squeezing

Abstract: This paper is built upon the deformation-assisted joining of sheets to tubes, away from the tube ends, by means of a new process developed by the authors. The process is based on mechanical joining by means of form-fit joints that are obtained by annular squeezing (compression) of the sheet surfaces adjacent to the tubes. The concept is different from the fixing of sheets to tubes by applying direct loading on the tubes, as is currently done in existing deformation-assisted joining solutions. The process is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As for boss forming [6], this process of indentation and injection can also be applied to both rods and tubes and in the case of rods, the axial compression applied by the punches will produce the indention and injection of the sheet material which will fill a circumferential slot machined in the rod (refer to Fig. 1a) without a radial deformation of the rod, as it observed for tubes under the same joining process [7]. The performance of joining by indentation and injection is limited to the remaining resistant cross-section after indentation, which is required to inject sufficient sheet material into the rod slot and produce a sound mechanical joint.…”
Section: Introductionmentioning
confidence: 99%
“…As for boss forming [6], this process of indentation and injection can also be applied to both rods and tubes and in the case of rods, the axial compression applied by the punches will produce the indention and injection of the sheet material which will fill a circumferential slot machined in the rod (refer to Fig. 1a) without a radial deformation of the rod, as it observed for tubes under the same joining process [7]. The performance of joining by indentation and injection is limited to the remaining resistant cross-section after indentation, which is required to inject sufficient sheet material into the rod slot and produce a sound mechanical joint.…”
Section: Introductionmentioning
confidence: 99%
“…The process should also prevent the formation of material protrusions above the sheet surface and the need for additional seal welding operations. As a result of this, the source of inspiration for the process to be presented in this paper was the work previously done by the authors in attaching metal sheets to metal tubes, away from the tube ends [ 12 , 13 ] ( Figure 2 ) and its subsequent extension to dissimilar materials [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of the joining by forming process shown in Figure 2 , allowed authors to conclude that a deformation zone parameter defined as the ratio of the sheet thickness to the cross-section recess length of the punch can be utilized to characterize plastic material flow inside the sheet thickness, and to establish the fundamental design guidelines to produce sound form-fit joints. Results showed that values of corresponding to mm and mm and entailing a combination of inhomogeneous and homogeneous plastic material flow could produce near symmetric sheet-tube contact interfaces with a good amount of material squeezed and sufficient constriction from the external undeformed regions of the sheets to prevent material from bending [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue of the journal Materials, 29 contributions to cutting-edge advances in different fields of the manufacturing engineering have been collected. In particular, in additive manufacturing and 3D printing [4][5][6][7][8][9][10][11]; sustainable and green manufacturing [12][13][14][15][16]; metrology and quality in manufacturing [17][18][19][20][21]; advances and innovations in manufacturing processes [22][23][24][25]; manufacturing of new materials [26][27][28]; design, modeling, and simulation in manufacturing engineering [29,30] industry 4.0 [31] and manufacturing engineering and society [32]. Among all of them, the topic additive manufacturing and 3D printing stands out for the number of contributions it has had in this Special Issue showing the interest that this topic arouses, currently, among researchers, the industry and the public in general.…”
mentioning
confidence: 99%
“…The next topics by the number of contributions are sustainable and green manufacturing and metrology and quality in manufacturing with five contributions each. The first one gathers four works about new sustainable lubrication/cooling techniques used in removal processes [12][13][14][15] and the other about reusing waste in ecological cement [16]. The second one collects research about the optimization of laser tracker location on verification process [17], estimation of an upper bound to the value of the step potentials from grounding resistance measurements [18], enhanced positioning algorithm by mesh elements, recalculation and angle error orientation [19], industrial calibration procedure for confocal microscopes [20] and, finally, the development and validation of a calibration gauge for length measurement systems [21].…”
mentioning
confidence: 99%